Security Force Assistance in Afghanistan Identifying Lessons for Future Efforts - Kelly, Terrence K. (RAND Corporation, 2011)
Security force assistance (SFA) is a central pillar of the counterinsurgency campaign being waged by U.S. and coalition forces in Afghanistan. This monograph analyzes SFA efforts in Afghanistan over time, documents U.S. and international approaches to building the Afghan force from 2001 to 2009, and provides observations and recommendations that emerged from extensive fieldwork in Afghanistan in 2009 and their implications for the U.S. Army.